Active learning using physical prototypes and serious games - Sousa, Rui M. (2013)
It is widely accepted that the “learning by doing” approach results in higher levels of knowledge retention. This paper describes how this subject is addressed in the Integrated Master degree on Industrial Engineering and Management (IEM) at University of Minho, Portugal. Serious games are used as a learning tool in different years of the IEM degree to illustrate and consolidate important concepts, namely production dynamics and performance issues. To reinforce “learning by doing” the development of physical prototypes was included in one of the IEM Project‐Led Education semesters involving the design of a production system using Lego® Mindstorms® NXT building blocks. This paper provides a reflection on the use of serious games and physical prototypes, mainly in terms of learning outcomes and, to a lesser extent, on students learning styles. Moreover, it provides some hints on the integration of the tools on the curricular structure and on its practical implementation.